Squiresville, Johnson County - Laidacker, Emmalee (Kansas State University, The Chapman Center for Rural Studies, 2015)
A. B. Squires established a large hotel in his new town of Squiresville, which became a destination for Union soldiers and stage line passengers until the end of the Civil War and construction of a nearby railroad closed down the town. This study includes census data, military records, newspaper articles, and photographs of the town site.
Emmalee Laidacker, “Squiresville, Johnson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/151.
Keywords: Squiresville; Johnson County; Quantrill's Raid; gambling; Bleeding Kansas; 7th Kansas Cavalry